Responses of Two Cocoa Varieties to Environmental Stress Conditions - Fuadati, Ayu Zahrotul; Prastowo, Erwin; Munawarti, Aminatun; Arimarsetiowati, Rina (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2025)
Environmental changes resulting from climate anomalies may have significant implications for the future of global cocoa sustainability. A study was conducted to investigate the responses of two different cocoa varieties, i.e., ICCRI 06H and ICCRI 08H, to various environmental conditions at the greenhouse scale. Two distinct factors, i.e., green-house microclimate and soil moisture level, were simulated in a split-split plot design. A glass box equipped with artificial light was installed to modify the ambient temperature and air humidity, providing two different conditions: inside (IB) and outside (OB) the glass box, assigned as the main plot. The performance of cocoa seedlings was tested as a subplot, and they were exposed to different soil moisture levels, i.e., 100% soil moisture (ETa1), 50% soil moisture (ETa2), and 25% soil moisture (ETa3), defined as sub-subplot. Data suggested a slight difference in daily air temperature and relative humidity fluctuations, in both plots, observed as a function of time. A higher response of the stomatal index and density, up to 20%, was found in the ETa3 treatment for ICCRI 08H. The stress simulation increased the ICCRI 08H proline by up to 36% and guaiacol peroxidase by 27% higher than ICCRI 06H.